The Teacher Activities In Managing Classroom At Junior High School - Raynaldo, Desri Raynaldo; Perpisa, Lili; Sesmiyanti, Sesmiyanti (EduCurio: Education Curiosity, 2024)
This research was descriptive qualitative study. The subject of this research was the English teacher at the seventh grade. The data was collected by using observation and interview. The result of this research show (1) Classroom management conducted is divided into five aspects. There were physical design of classroom orderly rows and separate table, rules and routines, relationships, engaging and motivating instruction, and discipline. (2) The Problem Faced by English Teacher in Classroom Management. Problems were unprepared material, motivation and students misbehavior. To solve the problem, the teacher gave a punishment and treatment